Autophagy in malignant transformation and cancer progression. (23rd February 2015) - Galluzzi, Lorenzo; Pietrocola, Federico; Bravo‐San Pedro, José Manuel; Amaravadi, Ravi K; Baehrecke, Eric H; Cecconi, Francesco; Codogno, Patrice; Debnath, Jayanta; Gewirtz, David A; Karantza, Vassiliki; Kimmelman, Alec; Kumar, Sharad; et al.
<x xml:space="preserve">Abstract</x> Autophagy has been described to have tumor‐suppressive as well as tumor‐promoting functions. This review discusses how stage and context alters the role for autophagy in cancer, and argues for further research prior to targeting autophagy in cancer therapy.